First Report of Influenza D Virus in Dairy Cattle in Pakistan - Sajid Umar; Aftab Ahmed; Sajjad Hussain Gulraiz; Shaban Muhammad; Jieshi Yu; Arslan Rasool; Renata Koviazina; Aysun Yilmaz; Huseyin Yilmaz; Benjamin D. Anderson (Viruses)
Influenza D virus (IDV) is a newly emerged zoonotic virus increasingly reported worldwide. Cattle are considered the main reservoir of IDV, although it was first isolated from pigs. IDV infects multiple animal species and contributes to the bovine respiratory disease complex (BRDC). To date, there has been no report on the presence and frequency of IDV among cattle herds in Pakistan. In this study, we collected nasal swabs from cattle and performed virological surveillance of IDV via qRT-PCR. Among 376 swab samples, IDV was detected in 9 samples (2.4%). Four dairy cattle farms were positive for IDV; two IDV-positive samples (two/nine, 22.2%) belonged to asymptomatic cattle, while seven IDV-positive samples (seven/nine, 77.8%) were from cattle showing respiratory clinical signs, including two with a recent history of abortion and mastitis. Partial sequences of the hemagglutinin–esterase-fusion gene of IDV were obtained from nine qRT-PCR-positive samples. Notably, all IDV strains in this study clustered within the D/OK lineages in phylogenetic analysis. A 98.8–99.6% genetic identity to its European and US counterparts indicates that the IDVs are closely related. The D/OK lineage of IDV was previously unreported in Pakistan. This is the first report of IDV in Pakistan. We confirmed that IDV is circulating among cattle herds in Pakistan. This study underscores the importance of virological surveillance to monitor the ecology of IDV for better animal and public health. The continued spread of IDV and its adaptation to various hosts necessitate further epidemiological studies.